Refugees from Athens. Russian philosophy of the turn of the XIX and XX century and the 'unknowableness of God' - Podstawski, Michał (Hybris, 2013)
When we analyze the turn of the XXth and XIXth century in the Russian philosophy we often use the term „silver age” to emphasize its rapid development during that time. It is well know that the Orthodox Church with its principles remained independent from philosophy for a long time. It is only during the „silver age” that the efforts were taken to properly recognise the type of relations combining faith and science. However, it turned out that, regarding this matter, the experience of the East cannot be translated into the language of Western philosophy. This is why the greatest thinkers of this period, such as Pavel Florensky and Vladimir Solovyov, had to undertake a tremendous task of constructing the intellectual foundations for their spiritual tradition. When it comes to summarizing this era, Lev Shestov wrote that in the European philosophy one can distinguish between two currents of thoughts. The first is the rational one that originates from Athens and is characteristic to the philosophy of the West. The second one comes from Jerusalem and is based on the Revelation, specifically – the miracles. It is characteristic to the thinking of the East. The question is whether Shestov properly grasped the core of the problem, and whether it is the Orthodox Church that is in fact closer to the Ancient Greek understanding of the philosophical reality.